ANALISIS PERBEDAAN ABNORMAL RETURN DAN VOLUMEPERDAGANGAN SAHAM SEBELUM DAN SESUDAH PILPRES 9 JULI 2014 (STUDI KASUS PERUSAHAAN MILIK BAKRIE GROUP DAN MNC GROUP) - Suharyati Suharyati; Sri Hermuningsih (JURNAL MANAJEMEN, 2014)
The purpose of this study to analyze the differences abnormal return and trading volume activity before and after pilpres 9 July 2014, at the company Bakrie Group and MNC Group. The results show: (1) There are no differences in average abnormal return before and after pilpres 9 Juli 2014 on the company Bakrie Group and MNC Group.The absence of a difference is becausereaction IDX to the pilpres 9 July 2014 is instantaneous and not prolonged. (2) There are no differences inaveragetrading volume activitybefore and after pilpres 9 Juli 2014 on the company Bakrie Group, but there are differences in average trading volume activitybefore and after pilpres 9 July 2014 on the companyMNC Group. The discrepancies in the company MNC Group is because investors MNC Group took profit rollicking tacking. While no differences in the company Bakrie Group is because investors Bakrie Group are not bothered by pilpres 9 July 2014. (3) The Company is more affected by pilpres 9 July 2014 is a company owned by MNC Group. Keywords: Abnormal Return,TradingVolumeActivity, Pilpres 9 July 2014.